Experimental study of the static and dynamic behavior of pre-stressed concrete subjected to shear loading. (1st May 2021) - Abdul-Rahman, Reem; Saletti, Dominique; Forquin, Pascal
Highlights: The confined shear strength of dry and wet ordinary concrete is investigated. A new Hopkinson set-up has been developed for dynamic Punch-Trough Shear tests. The confinement level is measured by means of an instrumented pre-stressed cell. Shear strength is sensitive to the confinement level, water content and loading rate. Abstract: In the present work, the static and dynamic shear strength of concrete is investigated by means of Punch-Through Shear (PTS) tests. This experimental method consists in applying an axial load to the central part of the specimen which generates shear stresses in the ligament of the sample. Prior to the shearing stage, the concrete sample is subjected to a lateral confinement pressure that is applied by pre-stressing a metallic cell and then inserting the sample in-between the cell jaws so the confinement stresses are transferred to the concrete specimen during the unloading. The originality of this method lies then in the fact that the level of confinement is better controlled than the experimental protocols which can be found in the literature. A standard hydraulic press was used to conduct quasi-static experiments whereas a modified Split Hopkinson Pressure Bar device was used to perform the dynamic tests. The confinement cell is instrumented with strain gages so the confinement level applied to the ligament of the concrete specimen is measured before and during the shearing stage. The results on two sets of samples (dry and wet) shows that the shear strength is sensitive to the water content with higher values for dry samples and to the applied loading rate, with higher values of dynamic shear strength compared to static ones for both concretes.